The challenge of valuing ecosystem services that have no material benefits. (May 2017) - Small, N.; Munday, M.; Durance, I.
Highlights: The term cultural ecosystem services could be discarded for the more self-explanatory non-material ecosystem services . Differentiating services to individuals from services to communities could be helpful when valuing these ecosystem services. Focussing on ecosystem service change rather than simply service delivery would facilitate the assessment of such ecosystem services. Effort to collate long-term socio-environmental datasets will be key to implementing more broadly the ecosystem service paradigm. Abstract: Since the Millennium Ecosystem Assessment, ecosystem service science has made much progress in framing core concepts and approaches, but there is still debate around the notion of cultural services, and a growing consensus that ecosystem use and ecosystem service use should be clearly differentiated. Part of the debate resides in the fact that the most significant sources of conflict around natural resource management arise from the multiple managements (uses) of ecosystems, rather than from the multiple uses of ecosystem services. If the ecosystem approach or the ecosystem service paradigm are to be implemented at national levels, there is an urgent need to disentangle what are often semantic issues, revise the notion of cultural services, and more broadly, practically define the less tangible ecosystem services on which we depend. This is a critical step to identifying suitable ways to manage trade-offs and promote adaptive management. Here we briefly review the problems associated with defining and quantifying cultural ecosystem services and suggest there could be merit in discarding this term for the simpler non-material ecosystem services . We also discuss the challenges in valuing the invaluable, and suggest that if we are to keep ecosystem service definition focused on the beneficiary, we need to further classify these challenging services, for example by differentiating services to individuals from services to communities. Also, we suggest that focussing on ecosystem service change rather than simply service delivery, and identifying common boundaries relevant for both people and ecosystems, would help meet some of these challenges.